The Effect Of Dangke Feeding On Body Mass Index In Male White Rats (Rattus Norvegicus) With Obesity From The Sprague Dawley Strain - Kamali, Aqma Sabrina Kamali; Asrini Safitri; Ahmad Ardhani Pratama; Aryanti R. Bamahry; Dian Fahmi Itami (Fakultas Kedokteran Universitas Malikussaleh, 2025)
Obesity is defined as a metabolic disorder characterised by an increase in body fat mass and can lead to various chronic diseases. Dangke, a traditional fermented food from Enrekang, contains lactic acid bacteria which have been shown to have the potential to aid weight loss (Jones et al., 2022). The objective of this study was to ascertain the impact of dangke administration on the Body Mass Index (Lee Index) in male Sprague Dawley obese white rats (Rattus norvegicus). The present study was an experimental laboratory study with a pre-post-test design, incorporating a control group. The study involved 30 rats, which were divided into three groups: control, low-dose treatment (1.8 g/200 g BW), and high-dose treatment (3.6 g/200 g BW). Dangke was administered the substance for a period of 14 days via a feeding tube. The subsequent analysis of the data employed a range of statistical tests, including the Shapiro-Wilk, Levene, Paired Sample T-test, and One Way ANOVA. The findings indicated that there was no statistically significant difference in the control group (p = 0.893). However, the low-dose (p = 0.001) and high-dose (p = 0.004) groups demonstrated a substantial decrease in the Lee Index, indicating a dose-dependent response. The results of the analysis of variance (ANOVA) test following treatment indicated a significant difference between the groups (p = 0.002). The LSD follow-up test revealed a significant difference between the control group and the two treatment groups, but not between the low and high doses. The present study concluded that dangke significantly reduced the Lee Index in obese rats, although increasing the dose did not provide a significant additional effect. It is hypothesised that Dangke has the potential to be an alternative fermented nutritional intervention to aid weight loss.